A Comparative Study between Malnourished and Well-nourished Diarrheal Children Suspected with Giardiasis - Abdalhadi Ali, Athraa; Fadhil Alyasari, Hadi; Hassan Noor, Muder (International Journal of Psychosocial Rehabilitation, 2020)
The present study was carried out during the period of January to June 2018 in Al-Hilla Province. The study included 100 samples, which were collected from diarrheal pediatric patients at ages ranging between 1 and 6 years old; 50 samples were taken from malnourished children (30 male, 20 female), and 50 samples were taken from well-nourished diarrheal children. The study patients were being submitted to the Maternity and Children and Al Nour Hospitals in Al-Hilla City. Study: Pediatric children and their samples were examined clinically and microscopically , clinically by the aid of the specialist physician and patients guided with the hospital record , and microscopically in the parasite laboratory of the hospitals.The present study revealed that the males were infected more than females with giardiasis (58.3% and 41.6%), respectively. Giardiasis occurred in a high percentage in the age group ranging from 5 to 6 years old (50%). It was more common in the rural areas than in the urban areas, which were 66.6% and 33.3%, respectively. The study obtained results that revealed that the type of diarrheal symptoms among Giardiasis-infected children varied from watery 7(58.3), fatty 2(16.6), bloody 1(8.3), mucus 1(8.3), and mixed 1(8.3), respectively.Furthermore, there were different percentages of Giardia infection among study pediatric individuals according to their feeding patterns. The breastfeeding rate for children under two years old was 33.3%, followed by artificial feeding (33.3%) and mixed feeding (16.6%), respectively. Whereas, in a multinutrition pattern, children (2-6 years old) were 16.6%.In addition, there were different percentages of Giardiasis co-infection: 8 cases (66.7%), whereas the solely infection of Giardia was 4 cases (33.3%).